The identity of Tanacetum urmiense (Anthemideae, Asteraceae) from northwestern Iran - Maroofi, Hosein; Rastegar, Azad; Tabad, Mohammad Aref (Phytotaxa, 2024)
Tanacetum urmiense Tabad, Maroofi & Rastegar (2022: 112) (Asteraceae) was established on the basis of three collections from Dalanpar Mountain, north-western Iran. The lack of mature achenes led the authors to mistakenly describe this species as a new Tanacetum. In the protologue, the authors stated that the new Tanacetum was related to T. hololeucum (Bornm.) Podlech (1986: 105) but differed in the following characters: plant height (5–12 cm vs. 10–18 cm); indumentum (glabrous or sparsely pubescent vs. densely appressed tomentose); basal leaves dimensions (35 × 12 mm vs. 15–80 × 10–25 mm); capitula diameter (10–20 × 20–30 mm vs. 8–10 × 6–7), and indumentum of the phyllaries (glabrous or sparsely pubescent vs. sparsely or densely hirsutulose).